Investigação das outras disfluências em indivíduos gagos em diferentes faixas etárias - Alonso, Sarah Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Other disfluencies are common disruptions to all speakers, including those who stutter and mainly reflect linguistic uncertainties and inaccuracies, aiming at expanding the understanding of the message. They can be classified as: interjection, hesitation, revision, unfinished words, phrase repetition, and non-monosyllabic word repetition. There are investigations on the prevalence and justifications for their occurrence of individuals' speech with typical development, syndromes or communication disorders. However, there is a gap in the national and international literature regarding the analysis of other disfluencies observed in the speech of individuals who stutter. The general objective of this study was to investigate and compare the frequency and typologies of other disfluencies in individuals diagnosed with neurodevelopment stuttering, in different age groups. 146 individuals from a database of the Laboratory of Studies, Evaluation and Diagnosis in Speech-Language Pathology (LEAD) and the Fluency Studies Laboratory (LAEF) participated. The participants were subdivided by lifespan, in four groups: Preschool Children Group (PCG), consisted of 40 children from 3 to 5 years old; School Children Group (SCG), consisted of 62 children from 6 to 9 years old; Adolescent Group (AG), consisted of 18 individuals aged 10 to 19 years old; Adult Group (ADG), consisted of 26 individuals aged 20 to 59 years. All participants underwent a speech fluency evaluation, using audiovisual records of the spontaneous speech sample with 200 fluent syllables and classified according to the Stuttering Severity Instrument - SSI-3 Protocol. Statistical analysis was conducted using SPSS version 20 software, with a significance level of 0.05. Results showed that the adult had a higher number of other disfluencies in relation to the preschool children group. The groups were similar regarding frequency of hesitation, this being the most prevalent typology in all groups. The interjection occurred more frequently in the adult group when compared to children, preschool children or school children. The revision typology was more prevalent in adults and school children when compared to preschool children. The repetition of speech segment occurred more frequently in adolescents when compared to preschool children, and they showed a lower amount of non-monosyllabic word repetition in relation to adolescents. Unfinished words occurred more frequently in school children than in preschool children. Therefore, it is concluded that the group of adults who stutter showed a higher frequency of other disfluencies, when compared to preschool children who stutter, specifically a higher number of interjection and revision. The number of other disfluencies interfered with the total number of disruptions in the flow of speech of individuals who stutter, regardless the age group. It is believed that these other disfluencies should be valued in the fluency evaluation and therapy to provide a reduction and consequent promotion in fluency and an improvement in the communication of these individuals.

As outras disfluências são rupturas comuns a todos os falantes, inclusive em indivíduos que gaguejam, e refletem principalmente as incertezas e imprecisões linguísticas, visando ampliar a compreensão da mensagem. Podem ser classificadas como: interjeição, hesitação, revisão, palavras não terminadas, repetição de frase, e repetição de palavras não monossilábicas. Há investigações sobre a prevalência e sobre as justificativas de sua ocorrência na fala de indivíduos com desenvolvimento típico, com síndromes ou com distúrbios da comunicação. No entanto, na literatura nacional e internacional, existe uma lacuna a respeito da análise das outras disfluências presentes na fala de indivíduos que gaguejam. O objetivo geral deste estudo foi investigar e comparar a frequência e as tipologias das outras disfluências em indivíduos com diagnóstico de gagueira do neurodesenvolvimento, em diferentes ciclos de vida. Participaram 146 indivíduos que pertencem ao banco de dados do Laboratório de Estudos, Avaliação e Diagnóstico Fonoaudiológico (LEAD) e do Laboratório de Estudos da Fluência (LAEF). Os participantes foram subdivididos por ciclo de vida, em quatro grupos: Grupo de Crianças Pré-Escolares (GPE), composto por 40 crianças de 3 a 5 anos; Grupo de Crianças Escolares (GE), composto por 62 crianças de 6 a 9 anos; Grupo de Adolescentes (GA), constituído por 18 indivíduos na faixa etária de 10 a 19 anos; Grupo de Adultos (GAD), formado por 26 indivíduos com idade entre 20 a 59 anos. Todos os participantes foram avaliados quanto à fluência da fala, por meio de registros audiovisuais da amostra de fala espontânea com 200 sílabas fluentes e classificados segundo o Protocolo do Instrumento de Gravidade da Gagueira (Stuttering Severity Instrument - SSI-3). A análise estatística foi realizada utilizando o software SPSS versão 20, com nível de significância de 0,05. Os resultados mostraram que o grupo de adultos manifestou maior quantidade de outras disfluências em relação ao grupo de crianças pré-escolares. Os grupos foram semelhantes quanto à frequência de hesitação, sendo esta a tipologia mais prevalente em todos os grupos. A interjeição ocorreu em maior quantidade no grupo dos adultos quando comparado ao de crianças pré-escolares ou escolares. A tipologia revisão foi mais prevalente em adultos e crianças escolares quando comparados com crianças préescolares. A repetição de segmento da fala ocorreu com maior frequência nos adolescentes quando comparados às crianças pré-escolares, e estes apresentaram menor quantidade de repetição de palavra não monossilábica em relação aos adolescentes. Palavra não terminada ocorreu com maior frequência nos escolares em relação aos préescolares. Portanto, conclui-se que o grupo de adultos com gagueira apresentou maior frequência de outras disfluências quando comparado às crianças pré-escolares que gaguejam, especificamente maior quantidade de interjeição e revisão. A quantidade das outras disfluências interferiu no total de rupturas do fluxo da fala em indivíduos que gaguejam, independente da faixa etária. Acredita-se que as outras disfluências devem ser valorizadas na avaliação da fluência e na terapia, com o intuito de propiciar sua redução e consequente promoção da fluência e melhora da comunicação nestes indivíduos.
Other disfluencies in individuals with stuttering in different age groups
Keywords: Evaluation studies; Stuttering; Preschool; Child; Adolescent; Adult; Estudos de avaliação; Gagueira; Pré-escolar; Criança; Adolescente; Adulto